Association between distance from the radiation source and radiation exposure: A phantom‐based study. Issue 6 (3rd September 2020) - Pancholy, Samir B.; Payne, Michael; Pancholy, Pariseema S.; Patel, Gaurav A.; Patel, Saurabh; Shah, Sanjay C.; Kaul, Prashant; Pancholy, Shivam A.; Patel, Tejas M.
Abstract: Objectives: The study evaluated the association between distance from radiation source and radiation exposure. Background: Radiation exposure during medical procedures is associated with increased risk of cancer and other adverse effects. Methods: An American National Standards Institute phantom was used to study the relationship between measured entrance surface exposure (MESE) and distance from the X‐ray source in postero‐anterior, left anterior oblique, and right anterior oblique projections. Three distance settings for table height were evaluated with "low" defined as 52 cm, "mid" 66 cm, and "high" 80 cm from the focal point of the X‐ray source. Air‐kerma and dose‐area product measurements were recorded. Operator exposure with each of these conditions was measured, in a short operator (150 cm) as well as in a tall operator (190 cm). Results: Aggregate results for the three projections were as follows. MESE (μGy/frame) significantly decreased as table‐height increases (median, interquartile range, p ‐value) (low table‐height 192.5 [122.4–201.2], mid table‐height 105.8 [82.7–115.8], and high table‐height 71.7 [58.4–75], p < .0005). The operator exposure (μGy/frame), significantly increased as the table‐height increased (low table‐height 0.0943 [0.0598–0.1157], medium table‐height 0.1128 [0.0919–0.1397], and high table‐height 0.158 [0.1339–0.2165], p < .0005). A shorter operator received higher radiation exposure compared to a taller operator (short operator 0.1405 [0.1155–0.1758] and tall operator 0.0995 [0.0798–0.1212], p < .0005). Conclusions: Increasing table‐height is associated with a significant decrease in MESE. Operator radiation exposure increases with increasing table‐height and shorter operators receive greater radiation exposure compared to taller operators.